The Use of STAD Cooperative Learning Model to Improve Reading Comprehension Skills of Junior High School Students - Rorimpandey, Rinny S.; Kartini, Kartini; Moybeka, Adolfina M. S. (English Education Department, 2024)
This study investigates the importance of English language learning in Indonesia, particularly focusing on reading comprehension among students at Kakaskasen Christian Junior High School. As English has become a global lingua franca, mastering it is essential for students to enhance their communication skills and improve their employability in an increasingly interconnected world. However, many students struggle with reading comprehension, as evidenced by assessments showing that only 7 out of 25 students met the minimum required score. The challenges identified include limited vocabulary, lack of engagement with reading materials, and ineffective teaching methods. To address these issues, the research advocates for the implementation of cooperative learning strategies, specifically the Student Teams Achievement Divisions (STAD) model. This approach encourages collaboration among students and fosters an interactive learning environment that can enhance their reading skills. The findings suggest that employing cooperative learning techniques can significantly boost student motivation and performance in reading comprehension, ultimately preparing them for future academic and career opportunities while promoting a deeper understanding of cultural diversity through language learning.